The Effect of Intense Match-Speed Exercises on Some Special Physical Abilities and Skills of Volleyball Players - Marwa Hussein Hasan; Huda Badwi Shbeeb (Indian Journal of Forensic Medicine & Toxicology, 2021)
Each of the sports has special requirements for female athletes to practice sporting activity, and these requirements develop through training based on scientific foundations to improve the level of physical and skill, and through the experience of researchers in the field of volleyball, they noticed weakness in the skills of serving and crushing during the match, in addition to that, the use of standardized physical exercises according to exercises strongly match the speed of the game during training performance and work in resistance training and according to the components of the training load, and the training is performed in high-intensity doses and develops the level of physical abilities and functional indicators, the aim of the research was to prepare exercises strongly match speed of the game for volleyball players, as well as to identify the effect of exercises strongly match speed of the game on some special physical abilities and on some skill abilities of volleyball players, and the researchers used the experimental approach in the pre and post-test of one experimental group, the research community was identified for the volleyball players for the training season 2020-2021, which numbered (12) players for one experimental group. Strong match speed exercises were applied to the research sample for a period of eight weeks with three training units per week. The SPSS statistical bag was used to process the data and obtain the results, including I found the importance of intense match-speed exercises, a positive effect on some special physical abilities and skills of volleyball players.